Gender Equality in the New Millennium: Goal or Gimmick? - ANTROBUS, PEGGY (Caribbean Quarterly, 2006)
At the Millennium Summit in September 2000 the largest gathering of world leaders adopted the UN Millennium Declaration, committing their nations to a new global partnership to reduce extreme poverty and setting out a series of time-bound targets, all with a deadline of 2015, that have become known as the Millennium Development Goals (MDGs). The Millenium Development Goals are now part of an international development framework which many countries in the Caribbean have signed on to. This paper addresses the question of how the Millenium Development Goals can be made to work to promote gender equality and empowerment in the Caribbean Community (CARICOM) region. The analysis here will not be limited to "gender equality and women's empowerment (MDG Goal 3). It will also highlight the gender dimensions of some of the other MDGs that closely related to women's equality and empowerment - as a means and as an outcome. Finally, the analysis and suggestions in relation to strategies "to ensure that gender inequalities are identified and addressed in the MDG monitoring process and in national policy responses from governments" will focus on Caribbean realities. Suggestions are made by drawing on the findings and insights on the linkages between global trends, development strategies (including the macroeconomic policy framework of structural adjustment) and their impact on poor women, and the ways in which we might now approach activist interventions toward the goal of gender equality and women's empowerment.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; caraïbes; cours; discipline; féminisme des caraïbes; féminismes noirs; histoire et politique; pol4022; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences de l'éducation; thématiques

Les sciences et la construction des identités sexuées. Une revue critique - Gardey, Delphine (Annales. Histoire, Sciences Sociales, 2006)
Cet article rend compte des travaux en sciences sociales qui se sont intéressés aux sciences et à leur rôle dans la construction des identités sexuées. Il poursuit trois objectifs : introduire à une réflexion sur ce qu’a été dans le passé le savoir sur la différence des sexes et sur ce qui constitue dans différents corpus de connaissances scientifiques le féminin et le masculin, les femmes et les hommes ; repousser au plus loin les frontières communément admises de la naturalité du corps féminin, interroger le « fait » ou le « donné » du sexe – d’autres diraient la matérialité et la discursivité du sexe ; insister sur les façons dont les sciences contemporaines se mêlent et s’emmêlent dans la construction des identités sexuées, en focalisant l’attention sur les travaux qui montrent comment les sciences et les techniques transforment littéralement les corps. Il n’est alors plus seulement question de fabrication des sexes et du genre, mais de redéfinition des frontières et des limites des corps. Au-delà de la contribution historienne à ces réflexions, l’article met en évidence l’affirmation d’un champ de recherche à l’intersection des études de genre et des études sociales des sciences et des techniques qui emprunte à des traditions disciplinaires et méthodologiques et définit de nouveaux objets et de nouvelles manières de faire les sciences sociales.
Number: 3
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; essentialisme; europe; france; féminisme radical; histoire et politique; identités LGBTQIA2+; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail